Isolation of pathogenic yeasts from the surface microbiota of anteaters held in captivity (Research, Society and Development, 2021)
The composition of the fungal microbiota in the fur of wild animals is still poorly known. Establishing microbiological parameters that allow predicting opportunistic infectious events in these animals can be useful in the preservation of endangered species. The aim of this investigation was to isolate and identify potentially pathogenic yeasts from the coat of anteaters kept in captivity. Twenty-seven anteaters, from the Parque Zoológico de São Paulo Foundation (FPZSP) and Quinzinho de Barros Municipal Park (Zôo-Sorocaba, SP) were surveyed. Fourteen specimens will be giant anteater (Mymercophaga tridactyla) and 13 anteater (Tamandua tetradactyla), of which 63% males and 37% females. The carpet square technique was used to obtain the skin samples. Isolated yeasts were identified by their morphological characteristics and by semi-automated ID-32C™ method. To describe the variables obtained through the research instrument, the frequency of occurrence was verified and the results were expressed in relative values. A total of 33 yeasts were isolated from the skin samples of the 27 anteaters. The yeast species isolated were: eight Candida guilliermondii (24.2%), three C. famata (9.1%), three C. kefyr (9.1%), two C. glabrata (6.1%), three Cryptococcus laurentii (9.1%), one C. humicola (3.0%), six Geotrichum candidum (18.2%), three Malassezia pachydermatis (9.1%), two Rhodotorula glutinis (6.1%) and two Trichosporon asahii (6.1%). It can be concluded that yeasts known to be pathogenic can colonize the integument microbiota of giant anteaters and anteaters kept in captivity and represent a potential risk of opportunistic infection for these animals.